First High-Density Linkage Map and Single Nucleotide Polymorphisms Significantly Associated With Traits of Economic Importance in Yellowtail Kingfish Seriola lalandi - Nguyen, Nguyen H.; Rastas, Pasi M. A.; Premachandra, H. K. A.; Knibb, Wayne (Frontiers in Genetics, 2018)
The genetic resources available for the commercially important fish species Yellowtail kingfish (Seriola lalandi) are relative sparse. To overcome this, we aimed 1) to develop a linkage map for this species, and 2) to identify markers/variants associated with economically important traits in kingfish (with an emphasis on body weight). Genetic and genomic analyses were conducted using 13,898 Single Nucleotide Polymorphism (SNPs) generated from a new high through-put genotyping by sequencing platform, Diversity Arrays Technology (DArTseq™) in a pedigreed population comprising 752 animals. The linkage analysis enabled to map about 4,000 markers to 24 linkage groups (LG), with an average density of 3.4 SNPs per cM. The linkage map was integrated into a genome-wide association study (GWAS) and identified six variants/SNPs associated with body weight (P< 5e-5) when a multi-locus mixed model was used. Two out of the six significant markers were mapped to linkage groups 17 and 23, and collectively they explained 5.8% of the total genetic variance. It is concluded that the newly developed linkage map and the significantly associated markers with body weight provide fundamental information to characterise genetic architecture of growth-related traits in this population of yellowtail kingfish S. lalandi.